การวิเคราะห์สถานการณ์การปฏิบัติงานของหน่วยปฏิบัติการฉุกเฉิน ในชุมชน อำเภอป่าแดด จังหวัดเชียงราย - พนาวัน พรหมเผ่า (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
An Emergency Operation Unit is a team which provides initial emergency care and aid. It consists of personnel with the necessary knowledge, experience and equipment to deal with emergency situations. A descriptive study was conducted to analyze the performance of 5 Emergency Operation Units operating in Pa Daet District, Chiang Rai Province, using the structure, process and outcome framework proposed by Avedis Donabedian (2003). Population and sample were both evaluated within study. The instruments used in the study were structured interviews for the Director of Disaster Prevention and Mitigation and the Head of the Emergency Operation Unit, plus 9 persons who were also from the Emergency Operation Unit. Nine health care personnel were process interviewed along with 10 staff from the Dispatch Center. In addition a focus group was conducted with 10 people who are first responders. Data were recorded using the 139 record form. Data were then analysed using content analysis and categorization. The study found that Pa Daet District Emergency Operation Unit worked with 4 local government units and 1 private unit. Structural analysis showed components; 1) institutional policy and performance-based emergency medical services, 2) emergency medical context of second line of command, according to local regulations and unit organization (with one of the 5 Units in the study was operating without a Director of Disaster Prevention and Mitigation), 3) four of the units had plans of action for 1-3 years, while 1 unit did not have a plan, 4) there were not enough first responders to cover all the work required, 5) tools, materials and equipment in operation were sufficient and effective 6) location of all units is convenient regarding travel access and operations in each unit can be accounted for, 7) all units use centralized manual operational records, 8) each unit has been uneven allocated, and 9) all units use centralized record form. The process analysis revealed; 1) the promotion of many forms of emergency medical systems, both formal and informal styles, 2) refreshing of training knowledge, but without fixed regularity, 3) standard guidelines developed from continued use and practice based on initial coordination before arriving at the emergency scene, during operation, and post-accident, and 4) a lack of emergency operations staff to complete sufficient performance. The results showed that 82.73% of the time, the unit arrived at the scene within 1-5 minutes; and were able to return to base within 16-30 minutes (53.24%). Of the patients who received treatment from the emergency response unit, 100% received bleeding prevention procedures/ primary care, 99.11% of the patients received respiratory support, appropriate bleeding prevention (72.66%), appropriate splint application (88.24%) but also found 1 incident where cardiac resuscitation was required but could not be performed . The results of this study will be used as the basis for planning the implementation of guidelines in the emergency medical services system, and regarding 2nd personnel management issues. This development should continue as well as monitoring and evaluation, in order to further promote operational efficiency.